مكانة المرأة في الحياة السياسيّة الجزائرية - نورالدين, تابليت (جامعة الوادي University el-oued, 2014)
حظيت المرأة الجزائرية حظوة كبيرة واهتماما خاصّا, وهو ما يترجمه إدراج مسألة ترقية حقوقها السياسية ضمن التعديل الجزئي للدستور سنة 2008, حيث أن مشاركة المرأة في الحياة السياسية تدخل في صميم الممارسة الديمقراطية كنهج حضاري وتفكير متطور، لا يقبل أن يحدّ من إرادة المرأة، لأنّ المجتمع المتحضّر يفرض منطق الإقصاء، مع العلم أن التجربة الجزائرية في مجال التكفل بقضايا المرأة، تتدرج ضمن تطبيق المواثيق والقوانين الدولية لحقوق الإنسان. Abstract : Algerian women enjoy a special attention which has been interpreted by the inclusion of the issue of upgrading their political rights within the partial amendment of the constitution in 2008. This amendment places the women s participation in political life at the core of the democratic practice as a civilized approach which does not accept the limitation of the women’s will. The civilized society refuses to impose the logic of exclusion and knowing that the Algerian experience in the field of women’s issues meets the application of international convention and human rights laws. ا
Keywords: التعديل الدستوري؛ الممارسة الديمقراطية؛ الحياة السياسية؛ مشاركة المرأة؛ حقوق الإنسان؛ القوانين الدوليّة.; constitutional amendment; democratic practice; Political life; women's participation; human rights; International laws.